Bifidobacterial Dominance of the Gut in Early Life and Acquisition of Antimicrobial Resistance - Diana H. Taft (American Society for Microbiology, 2018)
ABSTRACT Bifidobacterium species are important commensals capable of dominating the infant gut microbiome, in part by producing acids that suppress growth of other taxa. Bifidobacterium species are less prone to possessing antimicrobial resistance (AMR) genes (ARGs) than other taxa that may colonize infants. Given that AMR is a growing public health crisis and ARGs are present in the gut microbiome of humans from early life, this study examines the correlation between a Bifidobacterium-dominated infant gut microbiome and AMR levels, measured by a culture-independent metagenomic approach both in early life and as infants become toddlers. In general, Bifidobacterium dominance is associated with a significant reduction in AMR in a Bangladeshi cohort, both in the number of acquired AMR genes present and in the abundance of AMR genes. However, by year 2, Bangladeshi infants had no significant differences in AMR related to their early-life Bifidobacterium levels. A generalized linear model including all infants in a previously published Swedish cohort found a significant negative association between log-transformed total AMR and Bifidobacterium levels, thus confirming the relationship between Bifidobacterium levels and AMR. In both cohorts, there was no change between early-life and later-life AMR abundance in high-Bifidobacterium infants but a significant reduction in AMR abundance in low-Bifidobacterium infants. These results support the hypothesis that early Bifidobacterium dominance of the infant gut microbiome may help reduce colonization by taxa containing ARGs. IMPORTANCE Infants are vulnerable to an array of infectious diseases, and as the gut microbiome may serve as a reservoir of AMR for pathogens, reducing the levels of AMR in infants is important to infant health. This study demonstrates that high levels of Bifidobacterium are associated with reduced levels of AMR in early life and suggests that probiotic interventions to increase infant Bifidobacterium levels have the potential to reduce AMR in infants. However, this effect is not sustained at year 2 of age in Bangladeshi infants, underscoring the need for more detailed studies of the biogeography and timing of infant AMR acquisition.